2015
DOI: 10.1371/journal.pone.0130180
|View full text |Cite
|
Sign up to set email alerts
|

Experienced and Perceived Risks of Mycobacterial Diseases: A Cross Sectional Study among Agropastoral Communities in Northern Tanzania

Abstract: ObjectiveThe current study was conducted to assess experienced risk factors and perceptions of mycobacterial diseases in communities in northern Tanzania.MethodsWe conducted a cross-sectional study in Arusha and Manyara regions in Northern Tanzania. We enrolled tuberculosis (TB) patients attending Mount Meru Hospital, Enduleni Hospital and Haydom Lutheran Hospitals in Arusha municipality, Ngorongoro and Mbulu districts, respectively. Patient addresses were recorded during their first visit to the hospitals. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…There might be reasons to believe that Maasai pastoralists refused to accept diseases such as TB [especially human TB] because of the stigma it posed in some Maasai communities, where is sometimes associated with HIV/AIDS. A number of recent studies from similar groups and socio-ecological studies documented a gap in knowledge on the perceived causative agents of tuberculosis [ 48 , 49 , 61 ]. In their study about perceptions of tuberculosis among Maasai of Simanjiro, Haasnoot and colleagues [ 48 ] documented multiple reported causes of tuberculosis such as staying for long periods in strong sun, excessive exercise, smoking, promiscuity, breathing in dust and most reported that it was hereditary.…”
Section: Discussionmentioning
confidence: 99%
“…There might be reasons to believe that Maasai pastoralists refused to accept diseases such as TB [especially human TB] because of the stigma it posed in some Maasai communities, where is sometimes associated with HIV/AIDS. A number of recent studies from similar groups and socio-ecological studies documented a gap in knowledge on the perceived causative agents of tuberculosis [ 48 , 49 , 61 ]. In their study about perceptions of tuberculosis among Maasai of Simanjiro, Haasnoot and colleagues [ 48 ] documented multiple reported causes of tuberculosis such as staying for long periods in strong sun, excessive exercise, smoking, promiscuity, breathing in dust and most reported that it was hereditary.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the general lack of awareness of bTB, zoonotic TB (zTb) awareness was also very low in that 95.2% of participants had never heard of zoonotic TB and 95.8% had a poor understanding of zoonotic transmission (Table 2). The low awareness of the transmission of zoonotic TB in the pastoral society of Manyara, which has been reported by a number of previous studies is surprising but not unusual [11,27,28]. Lack of clear knowledge on zoonotic transmission risks society to poor handling of animals and animal products and highlights a need for campaigns with effective communication addressing human TB including risk of zoonotic transmission from livestock species.…”
Section: Discussionmentioning
confidence: 99%